Pengaruh Media Pembelajaran Berbasis Wordwall Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VII SMPN 1 Pasir Penyu - Riyanti, Asifa Ajeng Dwi; Effendi, Leo Adhar (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
The process of learning mathematics includes an important aspect that students must master, namely the ability to understand mathematical concepts. The conceptual understanding ability of students at SMPN 1 Pasir Penyu is still relatively low. This problem arises because learning activities tend to be teacher-centered, and there are limited opportunities for students to engage in activities that enhance their mathematical problem-solving skills. Therefore, this study aims to examine the effect of Wordwall-based learning media on the understanding of mathematical concepts among seventh-grade students of SMPN 1 Pasir Penyu. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of all Grade VII students in the 2025/2026 academic year. The sample was selected through purposive sampling, consisting of one experimental class with 32 students and one control class with 32 students. The research instruments included a mathematical concept understanding test and validated learning tools. Data were collected using both test and non-test techniques and analyzed through descriptive and inferential statistical methods. These revealed a significant difference in the average scores of students’ conceptual understanding between the experimental and control classes after being given different treatments. Based on the results of the Independent Sample T-Test, the obtained significance value (Sig. 2-tailed) was 0.000, which is less than α = 0.05. This means that H₀ is rejected and H₁ is accepted. Therefore, it can be concluded that the use of Wordwall-based learning media significantly improves students’ understanding of mathematical concepts in Grade VII of SMPN 1 Pasir Penyu.